The Effect of Education on the Management of the DM Diet with the Plate Method on the Knowledge and Behavior of Nutrition Management in People with Diabetes Mellitus - Renova Oktarini Br.Sibuea; Adrial Paskalis Ginting; Angelica Putri Pardosi; Jamelia Nifer Carin Tuakora; Fiolenty B.M Sitorus (Journal of Social Research, 2025)
Diabetes mellitus (DM) is a chronic condition characterized by elevated blood sugar levels beyond normal limits. Data from the Ministry of Health in 2023 showed that 5.7 million people in the Banten region have DM, with 1.59 million in Tangerang Regency. A major factor contributing to the high prevalence of DM is the lack of knowledge about DM diet management and poor nutrition management behavior among patients. This study aims to assess the effect of DM diet management education using the plate method on knowledge and nutritional behavior of DM patients in Bencongan Village, Tangerang Regency. A quasi-experimental one-group pretest-posttest design was used with 36 participants selected through purposive non-probability sampling. Instruments included a knowledge questionnaire from Dickson-Spillmann et al. (2011), an SMDM behavior questionnaire, a feedback sheet, and a plate method observation sheet. Data were analyzed using univariate and bivariate analyses with the Wilcoxon test. Results showed significant improvements in both knowledge and behavior (p = 0.000, <0.05), with 100% of participants demonstrating good knowledge and 97.2% showing good behavior post-intervention. Behavioral observations from the first to third visit indicated a 77.8% increase in appropriate nutrition management behavior. This study concludes that DM diet management education using the plate method effectively enhances knowledge and nutritional behavior in DM patients. Future research should include larger samples, long-term behavioral observation, and monitoring of compliance with the plate method in DM diet management.